Monitoring and strengthening of prestressed concrete cylinder pipes based on distributed acoustic sensing and iron-based shape memory alloys - Jianghao Ji; Hong Zhu; Zhiqiang Dong; Yijie Pan; Shitong Hou; Liping Cui (Underground Space, 2025)
This paper proposes an integrated system for monitoring and strengthening the prestressed concrete cylinder pipe (PCCP) with broken wires, which is based on distributed acoustic sensing (DAS) and self-prestressing iron-based shape memory alloy (Fe-SMA). This system was evaluated in a full-scale study on a PCCP with an inner diameter of 1400 mm and a length of 6000 mm. Firstly, the wire breakage signals were monitored by the DAS system. After that, the PCCP with broken wires were strengthened by Fe-SMA bars, and the mechanical properties were tested. The parameters such as different wire breakage ratios and self-prestressing degrees of Fe-SMA bars were also studied. The results show that the DAS system can identify the time and location of wire breakage; the wire breakage signal is characterized by high amplitude and short duration. After being prestressed with Fe-SMA bars, both the width and length of the main crack, as well as the strains in the concrete, mortar coating, and prestressed steel wires, significantly decreased. Additionally, the higher activation temperature of Fe-SMA bars can effectively offset the negative impact caused by the wire breakage development of PCCP. Combined Fe-SMA with the DAS monitoring system, it enables precise positioning and efficient strengthening of in-service PCCP with broken wires.